Catalyzing Food Systems Transformation: Highlights from SHiFT Work Package 5. - CGIAR (CGIAR, 2024)
There is no single solution to deliver sustainable healthy diets for all—instead, context-specific pathways for transformation need to be identified, co-designed, and supported at the national level to transform food systems toward sustainable healthy diets. Learn how the CGIAR Research Initiative on Sustainable Healthy Diets through Food Systems Transformation (SHiFT) is catalyzing food systems transformation in this video featuring Marion Herens, SHiFT’s Work Package 5 Lead.